Jejunal adenomyoma in a neonate, an extremely rare cause of neonatal bowel obstruction - Qusai Mashlah; Muhammad Eyad Ba'ath; Rawan Alhalabi, MD (Elsevier, 2022)
We report a case of jejunal adenomyoma in a neonate, found during exploratory surgery for bilious vomiting and feeding intolerance. This is the first reported case of neonatal jejunal adenomyoma as an isolated cause of intestinal obstruction.